Navigating Mathematics in the Metaverse: The M6 Learning Model and Its Impact on Different Learning Styles - Susandi, Ardi Dwi (Universitas Muhammadiyah Prof. DR. HAMKA, 2026)
Purpose: This study evaluates the effectiveness of the Metaverse-integrated M6 learning model on students' critical mathematical thinking skills across distinct learning styles, addressing the prevailing limitations of conventional, procedure-oriented instruction.Design/methodology/approach: A quantitative, quasi-experimental factorial design was utilized, categorizing students into an experimental cohort (M6-Metaverse) and a control group. Data were rigorously gathered via validated cognitive tests and learning style questionnaires, subsequently analyzed using a two-way ANOVA. Findings: The M6-Metaverse framework significantly outperformed conventional pedagogies in cultivating critical thinking. Furthermore, empirical results confirmed marked performance variations dictated by learning styles and established a significant interaction effect between the instructional model and learning preferences. Practical implications: Educators can proactively leverage the M6-Metaverse ecosystem as an adaptive pedagogical instrument to systematically accommodate diverse learning profiles while amplifying higher-order mathematical cognition. Originality/value: This research injects novel empirical insights into digital education by seamlessly synergizing the structured M6 instructional framework with immersive Metaverse technology, thereby advancing tailored, technologically-driven curriculum designs in mathematics. Purpose: Penelitian ini bertujuan menganalisis efektivitas model pembelajaran M6 terintegrasi Metaverse terhadap kemampuan berpikir kritis matematika berdasarkan gaya belajar, guna memecahkan masalah dominasi pengajaran prosedural konvensional. Design/methodology/approach: Studi kuantitatif kuasi-eksperimen berdesain faktorial ini membagi siswa ke dalam kelompok eksperimen (M6-Metaverse) dan kontrol (konvensional). Instrumen pengumpulan data meliputi tes berpikir kritis tervalidasi dan angket gaya belajar. Analisis data dieksekusi menggunakan uji ANOVA dua jalur. Findings: Model M6-Metaverse secara signifikan lebih efektif meningkatkan kemampuan berpikir kritis dibandingkan metode konvensional. Ditemukan perbedaan performa yang nyata berdasarkan gaya belajar, serta interaksi yang signifikan antara model pembelajaran dan gaya belajar siswa.Practical implications: Praktisi pendidikan dapat mengadopsi kerangka M6-Metaverse sebagai intervensi pedagogis adaptif untuk mengakomodasi heterogenitas preferensi belajar, sekaligus memacu keterampilan kognitif tingkat tinggi abad ke-21 pada siswa. Originality/value: Studi ini mempresentasikan kebaruan empiris dengan mensinergikan sintaks pedagogis M6 dan ekosistem imersif Metaverse, menghasilkan desain pembelajaran digital yang secara spesifik menjembatani karakteristik individu dengan kognisi matematis abstrak